2021
DOI: 10.3390/healthcare9070892
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Orthoses Prescription for Vertebral Fragility Fractures by Italian Physical and Rehabilitation Medicine Physicians: The SPIN-VER Survey

Abstract: Vertebral fragility fractures (VFFs) are the most common type of osteoporotic fractures, related to pain and disability. In this scenario, physical and rehabilitative medicine (PRM) physicians prescribe a patient-tailored rehabilitation plan, including spinal orthoses. However, there is a high heterogeneity in the clinical indications of spinal orthoses. Thus, the aim of this survey was to investigate common clinical practice in terms of the prescription of spinal orthoses. This nationwide cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Osteoporosis is associated with bone mass loss and deterioration of the microarchitecture of the bone and is caused by fragility fractures, which are related to severe pain, reduced social function, and decreased physical function [ 10 ]. For the treatment for osteoporosis and therapeutic management, rehabilitation management focuses on improving quality of life and includes strategies such as pain reduction, increased physical function, and independence of daily activities [ 11 , 12 ]. For example, some studies reported that occupational training and gradual strength training after surgery [ 11 , 13 , 14 ] and long-term care and management of patients through a health education program at home [ 11 , 15 ] were effective for managing osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is associated with bone mass loss and deterioration of the microarchitecture of the bone and is caused by fragility fractures, which are related to severe pain, reduced social function, and decreased physical function [ 10 ]. For the treatment for osteoporosis and therapeutic management, rehabilitation management focuses on improving quality of life and includes strategies such as pain reduction, increased physical function, and independence of daily activities [ 11 , 12 ]. For example, some studies reported that occupational training and gradual strength training after surgery [ 11 , 13 , 14 ] and long-term care and management of patients through a health education program at home [ 11 , 15 ] were effective for managing osteoporosis.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle Energy Technique (MET) appears to show little evidence of decreasing neck pain by improving cervical range of motion in chronic disorders, even when combined with a traditional rehabilitation approach [ 35 ]. In the elderly, given that VFF are the typical form of osteoporotic fractures, a proper management is mandatory in terms of pharmacological treatment and also of appropriate prescription of spinal orthoses in both acute and chronic VFF phase [ 36 ]. Furthermore, a vertical traction approach could counterbalance the boundaries of traditional (axial) traction treatment by preserving the physiological lumbar curve, without disproportionate stress on the posterior spinal structures [ 37 ].…”
Section: Evidence On Pain Management and Rehabilitation For Vertebral...mentioning
confidence: 99%
“…Specifically designed therapeutic exercises (i.e., early mobilization exercises, strengthening, and balance training) are beneficial for subjects with bone loss, improving their functioning and reducing the risk of falling. Another non-pharmacological therapeutic option is short-term use of the spinal orthoses [ 12 ], with potential positive effects on the muscle strength of the trunk extensors [ 13 ].…”
Section: Introductionmentioning
confidence: 99%